The Political Economy of Distress in East Asian Financial Institutions - Ferri, Giovanni, 1957- 1957- (The World Bank, 2000)
In the East Asian crisis, connections - with industrial groups or influential families - increased the probability of distress for financial institutions. Connections also made closure more, not less, likely, suggesting that the closure processes themselves were transparent. But larger institutions, although more likely to be distressed, were less likely to be closed, suggesting a too big to fail policy. - Politics and regulatory capture can play an important role in financial institutions' distress. East Asia's financial crisis featured many distressed and closed financial intermediaries in an environment with many links between government, politicians, supervisors, and financial institutions. This makes the East Asian financial crisis a good event for studying how such connections affect the resolution of financial institutions' distress. Bongini, Claessens, and Ferri investigate distress and closure decisions for 186 banks and 97 nonbank financial institutions in Indonesia, the Republic of Korea, Malaysia, the Philippines, and Thailand. They find that after July 1997, 42 percent of the institutions experienced distress (were closed, merged, or recapitalized, or had their operations temporarily suspended). By July 1999, 13 percent of all institutions in existence in July 1997 had been closed.